Synthesis & characterization of copper nanoparticles using LASIS and chemical reduction technique - Keyur Bhatt,; Ajay Desai,; Vishal Pillai,; Kavit Mehta, (IJRDO-Journal of Applied Science, 2019)
Nanotechnology refers to the creation and utilization of material whose constituents exist at the nano scale and by convention is up to 100nm in size. Nanotechnology explores electrical, magnetic and optical activity as well as structural behavior at the molecular and sub molecular level. The control over in particle size and in turn size dependent properties of copper nanoparticles is expected to provide additional applications. Various methods for synthesis of copper nanoparticles have been reported including chemical methods, physical methods, biological methods, and green synthesis. A detailed discussion on the synthesis of copper nanoparticles using LASIS and chemical reduction technique are mentioned and the characterization of synthesized copper nanoparticles is done by UV- Visible spectroscopy using Mie Theory for theoretical particle size estimation.